2021
DOI: 10.1111/jora.12668
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID‐19 Pandemic on Adolescent Emotional, Social, and Academic Adjustment

Abstract: The COVID‐19 pandemic has had a strong impact on adolescents worldwide. This special issue aimed to increase our understanding of the factors that explain interindividual differences in how adolescents are affected by the pandemic. The special issue includes 21 empirical articles from four continents on the role of the pandemic in changes in emotional, social, and academic adjustment during adolescence. The studies demonstrate that many adolescents experienced increased depressive symptoms, negative affect, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
97
1
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(112 citation statements)
references
References 50 publications
5
97
1
9
Order By: Relevance
“…Adolescence coincides with a key period of brain development and the formation of one’s personal and social identity [ 44 ]. Adolescents may be particularly vulnerable to public health preventive measures that can lead to disruptions in their social life [ 45 ], but, as they get older, may also be able to develop new coping strategies such as connecting with peers online and outdoors, and engaging in leisure and health-promoting activities. Younger youth, who may not have the means or capacity to develop the same coping mechanisms, appear to have been equally, if not more strongly affected by school closures and other pandemic-related measures, which may have contributed to the increase in MHR ED utilization seen in this age group [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adolescence coincides with a key period of brain development and the formation of one’s personal and social identity [ 44 ]. Adolescents may be particularly vulnerable to public health preventive measures that can lead to disruptions in their social life [ 45 ], but, as they get older, may also be able to develop new coping strategies such as connecting with peers online and outdoors, and engaging in leisure and health-promoting activities. Younger youth, who may not have the means or capacity to develop the same coping mechanisms, appear to have been equally, if not more strongly affected by school closures and other pandemic-related measures, which may have contributed to the increase in MHR ED utilization seen in this age group [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showing that children’s emotional difficulties decreased significantly, on average, during the Italian lockdown period, is in accord with the longitudinal studies reporting a stability or a significant decrease in emotional problems during the lockdown in the United Kingdom and Norway (Bignardi et al, 2020; Larsen et al, 2021). The lightened school load and curbed peer relational context, along with a positive and supportive family environment, probably facilitated a mood regulation in young adolescents during this isolation period (Branje & Morris, 2021). Besides, we need to specify that the post-COVID-19 data collection was in June, right when the situation in Italy started to improve and restrictions were loosened.…”
Section: Discussionmentioning
confidence: 99%
“…A significant increase in depression symptoms during the U.K. lockdown was observed in children and adolescents, but no significant changes in anxiety and emotional problems was reported (Bignardi et al, 2020). On the contrary, other studies reported positive findings, with a significant decrease in emotional reactions found in children in Norway together with a general increase in well-being in the United States (Branje & Morris, 2021;Larsen et al, 2021).…”
mentioning
confidence: 85%
“…Adolescence coincides with a key period of brain development and the formation of one’s personal and social identity. (43) Adolescents may be particularly vulnerable to public health preventive measures that can lead to disruptions in their social life,(44) but, as they get older, may also be able to develop new coping strategies such as connecting with peers online and outdoors, and engaging in leisure and health-promoting activities. Younger youth, who may not have the means or capacity to develop the same coping mechanisms, appear to have been equally, if not more strongly affected by school closures and other pandemic-related measures, which may have contributed to the increase in MHR ED utilization seen in this age group.…”
Section: Discussionmentioning
confidence: 99%